What beyond oil and gas? Russian trade specialisation in manufactures - Olga Garanina (Bank of Finland, Institute for Economies in Transition (BOFIT), 2008)
The objective of the paper is to study Russia's pattern of specialisation in the manufactures trade since 1998. Russia's global trade balance for manufactures is rapidly deteriorating. However, the trade pattern in manufactures should be differentiated according to Russia's main trading partners: the European Union (EU), the Commonwealth of Independent States (CIS) and China. On the basis of trade indicator analysis (revealed comparative advantages and Grubel-Lloyd index of intra-industry trade), we show that Russia is globally disadvantaged in the manufactures trade vis-à-vis the EU and China, and advantaged in the trade with the within the CIS. Russia is managing to expand its manufactured exports to other CIS countries. However, it is gradually losing its role of main supplier of capital goods in the post-Soviet space.
URN:NBN:fi:bof-201408072222
Keywords: F14; 330; international trade; trade specialisation; revealed comparative advantage; intra-industry trade; Russia